Pengaruh Literasi Ekonomi Terhadap Perilaku Konsumtif Siswa SMA Negeri 3 Palembang - Mona Mutiara Armalia; Chandra Kurniawan; Nova Pratiwi (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to find out how economic literacy influences consumer purchasing power at SMA Negeri 3 Palembang. Using a random sampling technique, 98 people participated in the survey. Tests and Questionnaires form the data collection methodology. This research is a quantitative research because it uses a linear regression technique for data analysis. Based on the research results, it is known that economic literature has a negative effect on consumer purchasing power at SMA Negeri 3 Palembang. Number -t count -t table (-9.638 < -1.985), and a significance of 0.05 (0.000 < 0.05) are factors that prevent Ho from being rejected. The results of the analysis show that the R Square is around 0.492 and the economic growth rate for consumer demand is 49.2%, with the addition of complementary factors.